Microscopic detection of chloroplast transgenic plastids using fluorescent probe - Shahid Nazir; Muhammad Sarwar Khan (Advancements in Life Sciences, 2018)
Background: Fluorescent marker genes have modernized many areas of molecular biology, specifically in plant biotechnology and genetic engineering studies. The use of fluorescent proteins permits the scientists to purify the desired clones visually in transformation work. Green fluorescent protein (gfp) derived from Aequorea victoria has been the most common and favorite fluorescent marker which is being widely used as a visual selection marker gene. It can be easily visualized under UV light without the involvement of any substrate and is non-destructive as well.